Implantação de jardim sensorial na escola municipal de ensino fundamental Paulo Freire, no município de Ilha Solteira - SP - Muniz, Emanuella Mosca [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Sensory garden is a space where the senses of the human body are stimulated: sight, touch, smell, hearing and taste. It awakens our gaze to nature from its minimalist form. This place of observation and interaction with the environment provides countless experiences, from the most basic ones, such as the care and maintenance of the garden, to a therapeutic experience, where contact with nature contributes to the improvement of mental health and emotional well-being. From there, the sensory garden became a tool of art therapy, a discipline that is based on the area of the arts and psychology. Art therapy in practice consists of the use of artistic, visual and sensory resources as therapeutic elements. This discipline was adopted in recent years in Municipal Elementary Schools, in the city of Ilha Solteira, where students who integrate art therapy classes have some deficit in the learning process. The activities developed provide an increase in self-esteem, self-confidence, bringing perception to the student himself that he is his transforming agent. This work presents the processes of implantation of a sensorial garden, as part of the Extension Project "Gardening and School Vegetable Garden as an Instrument of Perception of the Environment". In this work, all the processes for creating the garden are exposed, which were carried out together with the students. Despite all the resource limitations, the sensory garden met and exceeded expectations.

Jardim sensorial é um espaço onde são estimulados os sentidos do corpo humano: visão, tato, olfato, audição e paladar. Ele nos desperta o olhar para a natureza desde sua forma minimalista. Esse local de observação e interação com o meio ambiente proporciona inúmeras experiências desde as mais básicas como os cuidados e manutenção do jardim, como uma experiência de cunho terapêutico, onde o contato com a natureza colabora com a melhora da saúde mental e bem-estar emocional. A partir disso, o jardim sensorial tornou-se uma ferramenta da arteterapia, uma disciplina que é baseada na área das artes e da psicologia. A arteterapia na prática consiste no uso de recursos artísticos, visuais e sensoriais como elementos terapêuticos. Essa disciplina foi adotada nos últimos anos nas Escolas Municipais de Ensino Fundamental, da cidade de Ilha Solteira, onde os alunos que integram as turmas de arteterapia possuem algum defict no processo de aprendizagem. As atividades desenvolvidas proporcionam aumento da autoestima, autoconfiança, trazendo percepção ao próprio aluno de que ele é o seu agente transformador. Este trabalho traz os processos de implantação de um jardim sensorial, como parte do Projeto de Extensão "Jardinagem e Horta Escolar como Instrumento de Percepção do Meio Ambiente". Neste trabalho são expostos todos os processos para criação do jardim, que foram executados juntamente com os alunos. Apesar de todas as limitações de recursos o jardim sensorial correspondeu e superou as expectativas.
Implementation of a sensory garden in the municipal school of elementary education Paulo Freire, in the municipality of Ilha Solteira – SP
Keywords: Inclusion students; Art therapy; Sensory garden.; Alunos de inclusão; Arteterapia; Jardim sensorial